Spatio-temporal Dynamics of Land Use and Land Cover in the Alibori Basin in Northern Benin Republic (West Africa) - Alamou, Abraham Babatounde; Arouna, Ousséni; Oloukoi, Joseph (Geoplanning: Journal of Geomatics and Planning, 2023)
Forest ecosystems of the Alibori basin are subject to multiple anthropogenic pressures witch therefore modify their land use and their land cover. This research aims at analyzing the spatio-temporal dynamics of land use and land cover in the Alibori basin in Northern Benin. The methodological approach used is based on the diachronic analysis of land cover from Landsat 2, 7, and 8 satellite images acquired respectively in 1980, 2000, and 2020, and the evaluation of land cover change parameters (conversion rate, level of deforestation, intensity and speed of change of land cover units). The results obtained reveal that the number of classes has increased from 8 to 9 with the appearance of plantations between 1980 and 2000. Between 1980 and 2020 the basin recorded a degradation of forest formations and an anthrogenization of savannah formations. The intensity and speed of loss of area are quite rapid in dense dry forests, open forests, and wooded savannahs between 1980 and 2020. The average rate of deforestation decreased from 1.27% annually between 1980 and 2000 to 1.26% annually between 2000 and 2020.